Aerosol and Urban Land Use Effect on Rainfall Around Cities in Indo‐Gangetic Basin From Observations and Cloud Resolving Model Simulations. Issue 7 (12th April 2018) - Sarangi, Chandan; Tripathi, S. N.; Qian, Yun; Kumar, Shailendra; Ruby Leung, L.
Abstract: Coupling of urban land use land cover (LULC) and aerosol loading on rainfall around cities in the Gangetic Basin (GB) is examined here. Long‐term observations illustrate more rainfall at urban core and climatological downwind regions compared to the upwind regions of Kanpur, a metropolitan area located in central GB. In addition, analysis of a 15 day cloud resolving simulation using the Weather Research and Forecasting model also illustrated similar rainfall pattern around other major cities in the GB. Interestingly, the enhancement of downwind rainfall was greater than that over urban regions, and it was positively associated with both the urban area of the city and ambient aerosol loading during the propagating storm. Further, to gain a process‐level understanding, a typical storm that propagated northwestward across Kanpur was simulated using Weather Research and Forecasting under three different scenarios. Case 1 has realistic LULC representation of Kanpur, while the grids representing the Kanpur urban region were replaced by cropland LULC pattern in Case 2. Comparison illustrated that urban heat island effect caused convergence of winds and moisture in the lower troposphere, which enhances convection over urban region and induced more rainfall over the urban core compared to upwind regions. Case 3 is similar to Case 1 but lower aerosol concentration (by a factor of 100) over the storm region. Analysis shows that aerosol‐induced microphysical changes delay the initiation of warm rain (over the upwind region) but enhance ice phase particle formation in latter stages (over the urban and downwind regions) resulting in increase in downwind rainfall. Key Points: Probable enhancement of rainfall at urban and downwind regions relative to the rainfall upwind of major cities in Northern India is found Enhancement of downwind rainfall is influenced by both the urbanized area of the city and ambient aerosol loading during the storm Synergy between Urban heat island effect and aerosol microphysical effect results in increase of urban and downwind rainfall around cities